2006
DOI: 10.4315/0362-028x-69.10.2519
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Prevalence and Total Microbial and Spore Populations in Spices Imported to Japan

Abstract: A total of 259 samples of 40 types of spices were tested for Salmonella prevalence and total microbial and spore populations. Salmonella enterica serotypes Weltevreden and Senftenberg were isolated from a black- and red-pepper sample, respectively. Because Salmonella was not detected by the most-probable-number method, it indicated that at least one cell of the microorganism was present in 25 g of sample. The mean aerobic bacterial count was greater than 5.39 log CFU/g in turmeric, garam masala, curry powder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…Interestingly, in another Brazilian study, Salmonella Typhimurium was found in Brazil nut kernels (Freire & Offord 2002). Hara-Kudo et al (2006) investigated the prevalence of Salmonella in spices imported to Japan and purchased at retail shops in Tokyo. Of the 259 samples comprising 40 product types, two (0.8%) were contaminated with Salmonella, although at low concentrations.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, in another Brazilian study, Salmonella Typhimurium was found in Brazil nut kernels (Freire & Offord 2002). Hara-Kudo et al (2006) investigated the prevalence of Salmonella in spices imported to Japan and purchased at retail shops in Tokyo. Of the 259 samples comprising 40 product types, two (0.8%) were contaminated with Salmonella, although at low concentrations.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 98%
“…Although the intent was not to draw quantitative comparisons between the prevalence of contamination of domestic and imported produce, the different detection rates might reflect differences in conditions during pre-and post-harvest operations. Based on the studies included in the present review (Table 2), Salmonella-contaminated spices and herbs were also detected in surveys from Brazil (Moreira, Lourenção, Pinto, & Rall 2009), Japan (Hara-Kudo et al, 2006), India (Banerjee & Sarkar 2003), Trinidad (Rampersad et al, 1999), and Austria (Kneifel & Berger 1994). In the study of Moreira et al (2009) examining the microbial status of various commodities (basil, bay leaves, black pepper, cinnamon, clove, cumin, dehydrated green onion, dehydrated parsley, oregano) marketed in São Paulo, 13 (5.6%) of 233 samples were positive for Salmonella.…”
Section: Salmonella-related Outbreaks Caused By Spices and Herbsmentioning
confidence: 99%
“…Afl atoxins were detected in black pepper, turmeric, coriander, and nutmeg (McKee 1995 ). The results of surveys conducted more recently revealed an equally broad spectrum of microorganisms and bacterial counts and included pathogens as well (Abou Donia 2008 ;Banerjee and Sarkar 2003 ;Hara-Kudo et al 2006 ;Moreira et al 2009 ;Sagoo et al 2009 ;Sospedra et al 2010 ;Witkowska et al 2011 ).…”
Section: Microbiological Profi Le Of Spices: An Overviewmentioning
confidence: 95%
“…Salmonella was also reported in black and red pepper imported to and examined in Japan (Hara- Kudo et al 2006 ). In a study of the microbiological quality of herbs and spices from Mexican markets, the only foodborne pathogen detected in 304 samples of 5 different spices was B. cereus (Garcia et al 2001 ).…”
Section: Microbiological Profi Le Of Spices: An Overviewmentioning
confidence: 99%
“…In fact, some surveillance studies indicated that Salmonella spp. was present in the spice, and Hara- Kudo et al (2006) reported that 1.7% of red pepper (1 of 59 samples) and 2.4% of black pepper (1 of 42 samples) were contaminated with Salmonella. Moreira et al (2009) reported that 18.2% (12 of 66 samples) of black peppers were positive for Salmonella.…”
Section: Introductionmentioning
confidence: 98%